Evaluation of growth and survival of Indian major carp fry in aerated vis-a-vis non aerated ponds under different stocking densities - Jena, J K; Aravindakshan, P K; Mohanty, U K (Indian Journal of Fisheries, 2011)
Evaluation of growth and survival of Indian major carp fry in aerated vis-a-vis non aerated ponds under different stocking densities